Therapeutic approach for severe COVID-19 and immunocompromised patients. A case series. (2021) - Simioli, Francesca; Martino, Maria; Annunziata, Anna; Carannante, Novella; Fiorentino, Giuseppe
Abstract: Background: COVID-19 is a potentially critical infectious disease. Inflammatory response and disease severity may vary according to immune system status. The aim of this case series is to investigate different presentation of COVID-19 in immunocompromised patients. Methods: this is a single centre case series about 17 immunocompromised patients admitted to our respiratory department during the recent COVID-19 pandemic. White blood cell count, C reactive protein, interleukin 6, lymphocytic subpopulation count (CD4 +, CD8 +, CD20 + ) and immunoglobulin count (IgG, IgM, IgA) were measured at hospitalization. Results: the most common causes of immunosuppression observed in our severe COVID-19 population are hematological malignancies, immunosuppressant drugs for transplant, primary immunodeficiency and inflammatory bowel disease. Onset symptoms were fever (88%), cough (53%), dyspnoea (24%), asthenia (35%), anosmia and/or ageusia (17%), expectoration (12%). Compared to benign conditions, patients with malignancies show a lower lymphocytic count (490 vs 1100 cells/uL) and higher interleukin 6 (33 vs 13 pg/mL). Conclusions: immunocompromised patients are at risk of adverse outcome from COVID-19. Hematological malignancies and anti-CD20 therapies induce a high risk. Primary immunodeficiency and classical immunosuppressant such as calcineurin inhibitors and antimetabolites share an intermediate risk.